CRISPR Distribution within the Escherichia coli Species Is Not Suggestive of Immunity-Associated Diversifying Selection - Touchon, Marie (American Society for Microbiology, 2011)

(untitled)
In order to get further insights into the role of the clustered, regularly interspaced, short palindromic repeats (CRISPRs) in Escherichia coli, we analyzed the CRISPR diversity in a collection of 290 strains, in the phylogenetic framework of the strains represented by multilocus sequence typing (MLST). The set included 263 natural E. coli isolates exposed to various environments and isolated over a 20-year period from humans and animals, as well as 27 fully sequenced strains. Our analyses confirm that there are two largely independent pairs of CRISPR loci (CRISPR1 and -2 and CRISPR3 and -4), each associated with a different type of cas genes (Ecoli and Ypest, respectively), but that each pair of CRISPRs has similar dynamics. Strikingly, the major phylogenetic group B2 is almost devoid of CRISPRs. The majority of genomes analyzed lack Ypest cas genes and contain CRISPR3 with spacers matching Ypest cas genes. The analysis of relatedness between strains in terms of spacer repertoire and the MLST tree shows a pattern where closely related strains (MLST phylogenetic distance of <0.005 corresponding to at least hundreds of thousands of years) often exhibit identical CRISPRs while more distantly related strains (MLST distance of >0.01) exhibit completely different CRISPRs. This suggests rare but radical turnover of spacers in CRISPRs rather than CRISPR gradual change. We found no link between the presence, size, or content of CRISPRs and the lifestyle of the strains. Our data suggest that, within the E. coli species, CRISPRs do not have the expected characteristics of a classical immune system.